Effect of Canolla oil on productional traits in Japanies equail - Mohammed, Murad Kazem; Razouki, Raad Hatem; Ibrahim, Youssef Tawfiq; Ahmed, Mohammed Jabbar (Journal of agricultural, environmental and veterinary sciences, 2018)
Total of 150 birds of Japanese quail at 7 weeks of age were fed on five experimental diets for 12 weeks، contain different levels levels addition of canolla oil(0، 25، 50، 75، 100 ml/ Kg diet) to diet in productional traits of Japanies equail and the quality of producted eggs. The productional traits were conclude: egg production، egg weight، food intake، feed conversion coefficient. The 1st diet were used as control، 2nd & 3rd diets had 0.25% & 0.50% of Canolla oil the 4th & 5th diets were included 0.75% & 1% Canolla oil. The birds were randomly distributed into five treatments، each treatment with three replicates (10birds/rep). Results shoued no significant differences (P>0.05) in egg weight، egg production and food conversion ratio between the 1st and 4th، 5th diets while these parameters values were significantly reduced (P
Keywords: Colza oil; birds; eggs; Japanese quail